Surveying the Impact of Authentic and Pragmatic Marketing by Paradigm Shift on Brand Authenticity: A Case Study of Selected Islamic Azad Universities (Anzali, Tehran Markaz, and Tonekabon) - Zohreh Ali Esmaeli; Bahram Kheiri; Farzin Farahbod (Advances in Human-Computer Interaction)
The contextual changes of the present age have altered the former order of personal and social relations in such a way that the creation of a new order is accompanied by an epistemic crisis; the crisis of knowledge of new relationships has rendered past valuations inefficient and invalid. In this regard, Kotler considers authenticity as the most influential element in this era of achieving sustainable development and customer trust, and since the production of university knowledge is the key to sustainable development, today it is faced with quality issues. This study aimed to investigate the effect of two marketing strategies, namely, authentic marketing and pragmatic marketing, through paradigm shifts as a solution to the epistemic crisis of brand authenticity. The research method of this study is based on quantitative and descriptive survey. The case study consists of Iranian students of Islamic Azad Universities (IAUs) stratified random sampling and sample size based on Morgan table were 385 people. Data were collected and distributed by questionnaire. The structural equation modeling technique with partial least squares approach and SmartPLS2 software were used for data analysis. The findings indicate that both authentic marketing and pragmatic marketing are more effective on brand authenticity through paradigm shift.